Sports values in physical education for students: moral, competence, and status values - Yaumulhak, Affan; Ma'mun, Amung; Hambali, Burhan; Syarifatunnisa; Anira (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: Sports values arise because of sports activities. These values have a positive impact on personal development. If physical education at school incorporates sports values, it becomes extremely significant. Research Objectives: The purpose of this study is to investigate the role of sports values in physical education. Methods: This research employed a quantitative descriptive method and was conducted at a high school in Bandung City. The participants were all school students, totaling 425 students, consisting of 193 male and 232 female students aged 15–17 years. The students completed the questionnaire in approximately 15 minutes. The study used a questionnaire to measure physical education sports values, specifically the Youth Sport Values Questionnaire-2 (YSVQ-2). Data analysis was performed using the SPSS program. We conducted statistical analysis and additional testing to investigate differences in the obtained means. Findings/Results: The research findings highlight a substantial disparity in average scores among sports values, with moral values emerging as the highest. This underscores the pivotal role of physical education in fostering moral development, achieved through active participation in game scenarios and facilitated by appropriate teaching methodologies. However, the successful internalisation of sports values and the holistic development of students extend beyond the confines of the classroom, involving significant contributions from parents and the broader environment. These external factors play a crucial role in shaping students' personalities, both within and outside the school environment. Conclusion: Future research endeavours should focus on designing and implementing structured and systematic sports values programmes to further enhance our understanding and implementation of sports values in physical education. These programmes should provide students with tangible opportunities to objectively observe and engage with sports values, thereby fostering their integration into both educational settings and the wider community.